MUHAMMADIYAH STRATEGIC STEPS IN OVERCOMING THE COVID PANDEMIC 19 - Robie Fanreza; Mario Kasduri (Proceeding International Seminar of Islamic Studies, 2021)
The purpose of this study was to obtain information about Muhammadiyah's Strategic Steps in Overcoming the Covid Pandemic 19. This study used a literature study method with an inductive approach. Researchers deliberately chose various print and online media related to Muhammadiyah in dealing with Covid 19. The results of this study.  First, Muhammadiyah provided assistance to overcome Covid 19 with 78.6 billion worth of money. Second, Muhammadiyah also provides assistance in the form of experts or medical personnel, covid equipment, volunteers, scholarships, Muhammadiyah hospitals are used as covid services. Third, autonomous assemblies and institutions and organizations are also involved in overcoming covid 19. Keywords : Strategic, Muhammadiyah, and Pandemic covid 19